Cyber Extortion In Dark Web - Ashokkumar Sharma, Krishna; Ravindra Ekhande, Devesh; Anil Agrawal, Harshit; Ghinmine, Nikhil Rajendra; Arpan, Arpan; Dave, Vivek (Journal of Neonatal Surgery, 2025)
The Dark Web has surfaced as a critical mecca for cyber highway robbery, enabling cybercriminals to exploit encryption technologies similar as Tor, I2P, and Freenet to conduct lawless conditioning anonymously. This paper examines the growing trouble of cyber highway robbery, assaying crucial attack styles, perpetrators, and provocations. Cyber highway robbery takes multiple forms, including ransomware, Distributed Denial- of- Service( DDoS) attacks, data breaches, and blackmail, with cybercriminals using underground forums, translated dispatches, and cryptocurrency to shirk discovery. To classify these pitfalls, the study introduces a triplets frame comprising Technological Extortion( e.g., ransomware and DDoS- for- hire), Data Manipulation Extortion( e.g., data exposure and revision), and Cerebral highway robbery( e.g., sextortion and deepfake blackmail). The exploration explores the elaboration of highway robbery ways, from phishing swindles to automated Ransomware- as-a- Service( RaaS) and DDoS- for- Hire operations, with cryptocurrency playing a pivotal part in rescue payments and plutocrat laundering.Despite advancements in network business analysis, AI- driven anomaly discovery, and legal interventions, combating cyber highway robbery remains a challenge due to jurisdictional complications and anonymized felonious networks. This study highlights the need for amulti-faceted approach, including zero- trust security fabrics, transnational legal cooperation, and mindfulness juggernauts. By assaying real- world cases of REvil, DarkSide, and LockBit, this paper underscores the urgency of global intelligence- sharing and forensic advancements to alleviate cyber highway robbery pitfalls.